Extratidal stars and chemical abundance properties of two metal-poor globular clusters M53 (NGC 5024) and NGC 5053 - Chun, Sang-Hyun; Lee, Jae-Joon; Lim, Dongwook (The astrophysical journal, 2020)
We search for extratidal stars around two metal-poor Galactic globular clusters, M53 and NGC 5053, using the near-infrared APOGEE spectra. Applying the t-distributed stochastic neighbor embedding (t-SNE) algorithm on the chemical abundances and radial velocities results in identification of two isolated stellar groups composed of cluster member stars in the t-SNE projection plane. With additional selection criteria of radial velocity, location in the color-magnitude diagram, and abundances from a manual chemical analysis, we find a total of 73 cluster member candidates; seven extratidal stars are found beyond the tidal radii of the two clusters. The extratidal stars around the clusters tend to be located along the leading direction of the cluster proper motion, and the individual proper motion of these stars also seems to be compatible to those of clusters. Interestingly, we find that one extratidal star of NGC 5053 is located on the southern outskirts of M53, which is part of common stellar envelope by the tidal interaction between two clusters. We discuss the nature of this star in the context of the tidal interaction between two clusters. We find apparent Mg-Al anticorrelations with a clear gap and spread (∼0.9 dex) in Al abundances for both clusters, and a light Si abundance spread (∼0.3 dex) for NGC 5053. Since all extratidal stars have Mg-enhanced and Al-depleted features, they could be first-generation stars of two globular clusters. Our results support that M53 and NGC 5053 originated in dwarf galaxies and are surrounded by extended stellar substructures of more numerous populations of clusters.
Gesehen am 14.10.2020